2002
DOI: 10.1021/jf020204u
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Thermal Desorption GC/MS with Simultaneous Olfactory Evaluation for the Characterization and Quantification of Odor Compounds from a Dairy

Abstract: Few analytical methods exist that combine chemical and sensory analysis of odorous compounds in whole air. Volatile organic compounds were collected by sampling air downwind from a small dairy through sorbent tubes of Tenax TA and Carboxen 569. Samples were analyzed by thermal desorption into a cryotrap and subsequent gas chromatographic separation, followed by simultaneous olfactometry and mass spectrometry. Because compounds are concentrated during sampling, sensory analysis encountered compounds at a concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Sorbed water on CMS material not only affects trapping efficiency during sampling, but also significantly degrades laboratory analysis (29)(30)(31). In this study, 15 µL of water on sorbent tube typically resulted in complete loss of data from either shutdown of the instrument due to over pressurization (ice blockage), or chromatograms that were impossible to interpret due to shifting retention times, poor peak shape, and loss of resolution of compounds (see Supporting Information).…”
Section: Table 2 Recovery (%) and Rsd A Of Odorants From Sorbent Tubmentioning
confidence: 88%
“…Sorbed water on CMS material not only affects trapping efficiency during sampling, but also significantly degrades laboratory analysis (29)(30)(31). In this study, 15 µL of water on sorbent tube typically resulted in complete loss of data from either shutdown of the instrument due to over pressurization (ice blockage), or chromatograms that were impossible to interpret due to shifting retention times, poor peak shape, and loss of resolution of compounds (see Supporting Information).…”
Section: Table 2 Recovery (%) and Rsd A Of Odorants From Sorbent Tubmentioning
confidence: 88%
“…Even alternative air sampling techniques such as sorbent tubes (USEPA Method TO-17) have their own short comings especially when sampling in humid environments using molecular sieve sorbents (Helmig and Vierling, 1995;Gawlowski et al, 1999;Trabue et al, 2008a). Rabaud et al (2002) noted problems with excess water when sampling air from a dairy facility in California. While sorbent material such as Carbopack X have been shown to trap both volatile and semi-volatile compounds in humid environments (Trabue et al, 2008a), it is poor at trapping and quantifying alcohols (Kornacki et al, 2005) a key VOC from AFOs (Blunden et al, 2005;Filipy et al, 2006;Ngwabie et al, 2008;Sun et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that livestock odors were mostly due to VOCs and defined as a mixture of carbon-, sulfur-, and nitrogencontaining compounds produced during incomplete anaerobic fermentation of manure (Miller and Varel, 2001). Rabaud et al (2002) observed 20 odorous and nonodorous compounds in emissions downwind of a dairy, with concentrations varying from 0.55 to 320.20 mg m…”
Section: Introductionmentioning
confidence: 99%
“…The p-cresol is exempt from the ROG list due to its low reactivity, but it is recognized as a potential odor-causing compound emitted from livestock operations. In addition to ozone formation, odors from dairies and cattle feedyards are nuisances associated with VOC emissions (Rabaud et al, 2002). Volatile fatty acids, p-cresol, phenol, 4-ethylphenol, indole, skatole, and sulfur-containing compounds are identified as contributors of odors from animal feeding operations Koziel et al, 2006;Wright et al, 2005).…”
Section: Introductionmentioning
confidence: 99%